URGENCY OF MARRIAGE AGREEMENTS FOR ISLAMIC RELIGIONS IN CREDIT TRANSACTIONS WITH FINANCING INSTITUTIONS - Imran Bukhari Razif (Universitas Muhammadiyah Tangerang, 2021)
Regulations related to joint assets of husband and wife of Muslims are subject to the provisions of the Marriage Law and the Compilation of Islamic Law. The position of the compilation of Islamic law that is under the Marriage Law and the emergence of legal consequences on joint assets of husband and wife in terms of credit transactions with financial institutions are the basis for the urgency of making a marriage agreement. Where the marriage agreement must explicitly regulate the mixing or separation of joint assets between husband and wife. The goal is to achieve legal certainty regarding the rights and obligations of husband and wife regarding joint assets in the event of a credit transaction with a financing institution.Keywords: Marriage Agreement, Joint Assets, Compilation of Islamic Law, Marriage Law